ANAPHORA RESOLUTION AND REANALYSIS DURING L2 SENTENCE PROCESSING: Evidence from the Visual World Paradigm. Issue 4 (30th August 2016) - Cunnings, Ian; Fotiadou, Georgia; Tsimpli, Ianthi
Abstract : In a visual world paradigm study, we manipulated gender congruence between a subject pronoun and two antecedents to investigate whether second language (L2) learners with a null subject first language (L1) acquire and process overt subject pronouns in a nonnull subject L2 in a nativelike way. We also investigated whether L2 speakers revise an initial interpretation assigned to an ambiguous pronoun when information in the visual context subsequently biased against it. Our results indicated both L1 English speakers and Greek L2 English speakers rapidly used gender information to guide pronoun resolution. Both groups also preferentially coindexed ambiguous pronouns to a sentence subject and current discourse topic, despite the fact that overt subject pronouns in the learners' L1 index a topic shift. We also observed that L2 English speakers were less likely to revise their initial interpretation than L1 English speakers. These results indicate that L2 speakers from a null subject background can acquire the interpretive preferences of overt pronouns in a nonnull subject L2. The eye-movement data indicate that anaphora processing can become qualitatively similar in native and nonnative speakers in the domain of subject pronoun resolution, but indicate reanalysis may cause difficulty during L2 processing.